Clinical and laboratory differences between early- and late-onset systemic sclerosis: A comparative analytical study. - Madiha Noor; Tehreem Sultana Hamid; Shahida Perveen; Haris Gul; Saba Samreen; Babur Salim (The Professional Medical Journal, 2026)
Objective: To compare the clinical and laboratory changes between early- and late-onset systemic sclerosis. Study Design: Comparative Analytical Cross-sectional study. Setting: Fauji Foundation Hospital (FFH), Rawalpindi (RWP). Period: 1st September, 2025 to February, 2026. Methods: A non-probability consecutive sampling was applied to recruit 100 individuals with confirmed ‘systemic sclerosis’ (SSc). Patients were recruited and categorized as Early Onset SSc (EOSSc) (onset ≤ 40 years) and Late Onset SSc (LOSSc) (onset >50 years). Groups were compared using t-test, chi-square, and fisher's exact test with significance set at p ≤0.05. Results: Mean age was 32.4 ± 5.1 years in EOSSc and 52.7 ± 6.3 years in LOSSc (p < 0.001). EOSSc had more diffuse cutaneous involvement than LOSSc (p < 0.001). EOSSc increased inflammatory markers (p = 0.01; p = 0.002). Anti-Scl-70 was more prevalent in EOSSct (p < 0.001), whereas anti-centromere antibodies were more frequent in LOSSc (p < 0.001). Pulmonary arterial hypertension (p = 0.01), interstitial lung disease (p = 0.04), and renal involvement (p = 0.02) were more frequent in LOSSc. Conclusion: There are clinical and serological patterns that are associated with age at the onset of the disease in SSc. Early onset disease is more diffuse in nature, with skin inflammation, but the late onset disease has increased prevalence of vascular and organ complications.